1999
DOI: 10.1002/(sici)1097-4547(19990501)56:3<307::aid-jnr10>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-changes of brain synapses and synaptic plasticity in response to an enriched environment

Abstract: Numerical synaptic density and synaptic vesicle density in rat frontal cortex were examined by electron microscopy as a function of age. The density of axospinous synapses, a major population of synapses, was found to peak at age 1 month, and to gradually decrease with aging. The synaptic vesicle density in axospinous synapses was shown to rapidly increase to a peak during the first 3 weeks and then decrease to the adult level, which remained unchanged in senescence. The time course of synaptic changes in agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…In contrast to the established phenomenon of synaptic loss with age 5, 27 , histological evidence for aging-related cell type composition change, specifically neuronal loss, remains unclear. Multiple stereological studies of the primate cortex have reported no aging-related neuronal loss 28, 29 .…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to the established phenomenon of synaptic loss with age 5, 27 , histological evidence for aging-related cell type composition change, specifically neuronal loss, remains unclear. Multiple stereological studies of the primate cortex have reported no aging-related neuronal loss 28, 29 .…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that changes in the methods of enrichment and rearrangement of objects in space and time are required for the sustained beneficial effects on the brain of the complex environment devoid of running wheels; but substantial evidence is still required to establish this hypothesis. Some EE studies failed to mention whether the objects were changed (Nakamura et al, 1999; Kempermann et al, 2002; Lazarov et al, 2005). If the objects were not replaced regularly to maintain novelty, it may have affected the immune response and behavior of rodents during study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors observed no change in the number of synapses after enrichment, suggesting that enrichment improves synaptic plasticity by strengthening the synapses, not by formation of new synapses (Nakamura et al, 1999). An increase in play behavior, aggression and locomotor activity was observed in studies primarily investigating immunological alterations in mice after enriching them in complex cages furnished with a variety of items (Marashi et al, 2003, 2004).…”
Section: Environmental Enrichmentmentioning
confidence: 96%
“…Several authors have described age-related synaptic loss in different brain structures such as the rat frontal cortex (Nakamura et al, 1999), sensory motor cortex (Markus and Petit, 1987), and Hp (Bondareff and Geinisman, 1976; Geinisman, 1979), with an ensuing decrease in NMDA-dependent glutamatergic transmission in rat Cx and Hp with age (Tamaru et al, 1991). Although synaptic loss might occur in the absence of neuronal loss, it would be a necessary consequence of the neuronal loss described here.…”
Section: Discussionmentioning
confidence: 99%